Outcome of Schatzkar Type VI Tibial Plateau Fractures Treated with Ilizarov External Fixator (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To analyze the results of schtzkar type VI tibial fractures treated with ilizarov external fixator.Methods: This study was conducted at Mardan Medical Complex from January 2015 to December 2017.All patients with Schatzker Type VI tibial plateau fractures meeting the inclusion criteria were treated with Ilizarov fixator. Outcome was assessed with radiology for fracture reduction and union and functionally with Knee Society Score(KSS).Results: Total 26 patients with tibial schatzkar type VI fractures were included in the study. Fifteen patients were open and 11 were closed fractures .Ilizarov external fixator was applied under image intensifier. All patients incurred Schatzker Type VI tibial plateau fractures caused by motor vehicle accident (12 patients), motorcycle accident (6 patients), pedestrian and automobile (8 patients). Five patients had Gustilo Grade IIIA open fractures, 10 had Gustillo type II open factures. Post operatively all the fractures healed. Assessment with knee society score showed fair result in 46.1 %( 12) patients, good in 30.7%(8),excellent in 15.3%( 4) and poor in 7.6%( 2) patients.Conclusion: Ilizarov external fixator is better treatment option for the schtzkar type VI fractures as adequate reduction, wound care and early mobilization not only reduces knee stiffness but leads to early fracture union.